Challenges and Opportunities of Fe‐based Core‐Shell Catalysts for Fischer‐Tropsch Synthesis. Issue 19 (12th August 2022) - Agwara, Jane N.; Bakas, Nikki J.; Neidig, Michael L.; Porosoff, Marc D.
Abstract: Fe‐based catalysts are an active, selective, and low‐cost option for tuning Fischer‐Tropsch synthesis (FTS) selectivity toward desirable light olefins. By encapsulating Fe within ZSM‐5, the resultant core‐shell catalysts have the potential to control the product distribution via secondary reactions that occur over the acid sites of the zeolite shell. In this paper, Fe is encapsulated within ZSM‐5 via the seed‐directed growth technique and characterized with a suite of analytical techniques including Mössbauer spectroscopy and X‐ray absorption fine structure (XAFS). Characterization of the core‐shell catalysts indicates that some of the Fe‐based active phase is destabilized during seed‐directed growth, demonstrating the challenges associated with encapsulating an Fe‐based active phase within zeolites. However, comparing FTS performance of the core‐shell catalyst with the Fe‐based control synthesized via incipient wetness impregnation demonstrates improved selectivity toward the desired C2 ‐C4 olefins and C5+ hydrocarbons. Abstract : Tuning the reaction selectivity of Fischer‐Tropsch synthesis over Fe‐based catalysts toward desirable light olefins and long‐chain hydrocarbons may be achieved through secondary reactions over a zeolite support. Encapsulating Fe within ZSM‐5 can enable further control over the product distribution upon stabilization of the desired Fe‐based active phase within ZSM‐5.